Permanent reorganization of Ia afferent synapses on motoneurons after peripheral nerve injuries - Alvarez, Francisco J. (2010)
After peripheral nerve injuries to a motor nerve the axons of motoneurons and proprioceptors are disconnected from the periphery and monosynaptic connections from group I afferents and motoneurons become diminished in the spinal cord. Following successful reinnervation in the periphery, motor strength, proprioceptive sensory encoding, and Ia afferent synaptic transmission on motoneurons partially recover. Muscle stretch reflexes, however, never recover and motor behaviors remain uncoordinated. In this review, we summarize recent findings that suggest that lingering motor dysfunction might be in part related to decreased connectivity of Ia afferents centrally. First, sensory afferent synapses retract from lamina IX causing a permanent relocation of the inputs to more distal locations and significant disconnection from motoneurons. Second, peripheral reconnection between proprioceptive afferents and muscle spindles is imperfect. As a result, a proportion of sensory afferents that retain central connections with motoneurons might not reconnect appropriately in the periphery. A hypothetical model is proposed in which the combined effect of peripheral and central reconnection deficits might explain the failure of muscle stretch to initiate or modulate firing of many homonymous motoneurons.